(untitled) (Bangladesh Journal of Physics, 2026)
The migration of neutrons from their generation point to the absorption point in a light water was analyzed using the Monte Carlo method. Neutron age (NA) of fast neutrons and the diffusion area (DA) of thermal neutrons were calculated as functions of temperature (20 – 100 °C), pressure (2 - 10 MPa), and boron concentration (200 - 1000 ppm), as well as their combined effects. NA and DA at room temperature and pressure have been calculated, and the results are consistent with experimental values. The percentage changes in average NA and DA per unit increase of boron concentration, temperature, and pressure have been estimated. In all cases, the amount of DA change was larger than that of the NA change. The percentage decreases of average NA and DA per fixed amount increment of temperature, pressure, and their combined increment were evaluated with 1000 ppm boron in the medium. Maximum average NA and DA decrements were 2.7% and 64.4%, respectively, at room temperature. This investigation provides critical insights into reactor safety and efficiency by quantifying how boron concentration, temperature, and pressure affect neutron migration in light water systems using MCNP. Bangladesh Journal of Physics, Vol. 32, Issue 2, pp. 53 – 65, December 2025